Cholinergic white matter pathways make a stronger contribution to attention and memory in normal aging than cerebrovascular health and nucleus basalis of Meynert - Nemy, Milan; Cedres, Nira; Grothe, Michel J; Muehlboeck, J-Sebastian; Lindberg, Olof; Nedelska, Zuzana; Stepankova, Olga; Vyslouzilova, Lenka; Eriksdotter, Maria; Barroso, José; Teipel, Stefan; Westman, Eric; et al. (NeuroImage, 2020)
The integrity of the cholinergic system plays a central role in cognitive decline both in normal aging and neurological disorders including Alzheimer's disease and vascular cognitive impairment. Most of the previous neuroimaging research has focused on the integrity of the cholinergic basal forebrain, or its sub-region the nucleus basalis of Meynert (NBM). Tractography using diffusion tensor imaging data may enable modelling of the NBM white matter projections. We investigated the contribution of NBM volume, NBM white matter projections, small vessel disease (SVD), and age to performance in attention and memory in 262 cognitively normal individuals (39-77 years of age, 53% female). We developed a multimodal MRI pipeline for NBM segmentation and diffusion-based tracking of NBM white matter projections, and computed white matter hypointensities (WM-hypo) as a marker of SVD. We successfully tracked pathways that closely resemble the spatial layout of the cholinergic system as seen in previous post-mortem and DTI tractography studies. We found that high WM-hypo load was associated with older age, male sex, and lower performance in attention and memory. A high WM-hypo load was also associated with lower integrity of the cholinergic system above and beyond the effect of age. In a multivariate model, age and integrity of NBM white matter projections were stronger contributors than WM-hypo load and NBM volume to performance in attention and memory. We conclude that the integrity of NBM white matter projections plays a fundamental role in cognitive aging. This and other modern neuroimaging methods offer new opportunities to re-evaluate the cholinergic hypothesis of cognitive aging.
Keywords: Neural Pathways; lidé; Middle Aged; sexuální faktory; Adult; nucleus basalis Meynerti; Cognition; Sex Factors; stárnutí; Diffusion Tensor Imaging; Female; pars basalis telencephali; Attention; věkové faktory; Memory; Humans; Cholinergic system; Basal Forebrain; zobrazování difuzních tenzorů; pozornost; paměť; lidé středního věku; mužské pohlaví; White Matter; Basal forebrain; Basal Nucleus of Meynert; Normal aging; nervové dráhy; ženské pohlaví; Aging; Age Factors; Magnetic resonance imaging; Male; Aged; bílá hmota; dospělí; Small vessel disease; senioři